Avaliação de pacientes ambulatoriais em uso de anticoagulantes orais - Santana, Ana Paula Bagesteiro (2006)
Trombotic diseases are a global health problem of multifactorial and multigenic etiology. They are characterized by the acute formation of trombus in veins and arteries. The oral anticoagulants are applied in order to create a partial deficiency on the active form of vitamin K, a co-factor in the changing of the factors of vitamin K-dependents coagulation, so that the risk of an abnormal coagulation can be reduced. The anti-vitamin K drugs or oral anticoagulants avoid the carboxylation of the II, VII, IX and X coagulation factors leading to the synthesis of the inactive factors. Several substances can change the action of oral anticoagulants, decreasing their action and increasing the thrombotic risk or increasing their activity and enlarging the blooding risk. The laboratory control of the oral anticoagulation is accomplished through the Time of Protrombine (TP) and of the Partial Thromboplastin Time (TTP) which are responsible for the success and safety of this therapeutic procedure. The present work has analyzed the parameters regarding the laboratory accompaniment of patients in use of oral anticoagulants as well as their interference on the medicine effect aiming to reach a better security for this kind of treatment. We can notice that most of the patients have made use of a quite rich diet in vitamin K producing variations in the values of their Normalized International Reasons (INRs) and consequently a larger difficulty in finding the right dose of the medicine for each patient. It also may be concluded that the anticoagulants response is influenced by some factors and those ones must be considered as, for example, the use of other medicines which affects the release or the absorption of the drug, laboratory technical troubles and the individual variability of each patient in relation to the drug.